Characterization of Squamosa-Promoter Binding Protein-Box Family Genes Reveals the Critical Role of MsSPL20 in Alfalfa Flowering Time Regulation - Ma, Lin; Liu, Xiqiang; Liu, Wenhui; Wen, Hongyu; Zhang, Yongchao; Pang, Yongzhen; Wang, Xuemin (Frontiers in Plant Science, 2022)
SQUAMOSA Promoter-binding protein-Like (SPL) genes affect a broad range of plant biological processes, and show potential application in crop improvement by genetic modification. As the most widely planted forage crop in the world, biomass and abiotic stresses tolerance are important breeding targets for alfalfa (Medicago sativa L.). Nevertheless, the systematic analysis of SPL genes in alfalfa genome remains lacking. In the present study, we characterized 22 putative non-redundant SPL genes in alfalfa genome and uncovered the abundant structural variation among MsSPL genes. The phylogenetic analysis of plant SPL proteins separated them into ten clades and clade J was an alfalfa specific clade, suggesting SPL genes in alfalfa might have experienced gene duplication and functional differentiation within the genome. Meanwhile, 11 MsSPL genes with perfect matches to miRNA response elements (MREs) could be degraded by miR156, and the cleavage sites were gene specific. In addition, we investigated the temporal and spatial expression patterns of MsSPL genes and their expression patterns in response to multiple treatments, charactering candidate SPL genes in alfalfa development and abiotic stress tolerant regulation. More importantly, overexpression of the alfalfa specific SPL gene (MsSPL20) showed stable delayed flowering time, as well as the increased biomass. Further studies indicated that MsSPL20 delayed flowering time by regulating the expression of genes involved in floret development, including HD3A, FTIP1, TEM1 and HST1. Together, our findings provide valuable information for future research and utilization of SPL genes in alfalfa, and elucidate a possibly alfalfa specific flowering time regulation, thereby supplying candidate genes for alfalfa molecular-assisted breeding.